High troponin levels in patients hospitalized for coronavirus disease 2019: a maker or a marker of prognosis?. Issue 11 (13th November 2021) - Ghio, Stefano; Montalto, Claudio; Pagnesi, Matteo; Lupi, Laura; Cappelletti, Alberto; Baldetti, Luca; Baldi, Enrico; Lombardi, Carlo; Metra, Marco; Perlini, Stefano; Oltrona Visconti, Luigi
Abstract : Aims: Controversial data have been published regarding the prognostic role of cardiac troponins in patients who need hospitalization because of coronavirus disease 2019 (COVID-19). The aim of the study was to assess the role of high-sensitivity troponin plasma levels and of respiratory function at admission on all-cause deaths in unselected patients hospitalized because of COVID-19. Methods: We pooled individual patient data from observational studies that assessed all-cause mortality of unselected patients hospitalized for COVID-19. The individual data of 722 patients were included. The ratio of partial pressure arterial oxygen to fraction of inspired oxygen (PaO2 /FiO2 ) and high-sensitivity troponins was reported at admission in all patients. This meta-analysis was registered on PROSPERO (CRD42020213209). Results: After a median follow-up of 14 days, 180 deaths were observed. At multivariable regression analysis, age [hazard ratio (HR) 1.083, 95% confidence interval (CI) 1.061–1.105, P < 0.0001], male sex (HR 2.049, 95% CI 1.319–3.184, P = 0.0014), moderate-severe renal dysfunction (estimated glomerular filtration rate < 30 mL/min/m 2 ) (HR 2.108, 95% CI 1.237–3.594, P = 0.0061) and lower PaO2 /FiO2 (HR 0.901, 95% CI 0.829–0.978, P = 0.0133) were the independent predictors of death. A linear increase in the HR was associated with decreasing values of PaO2 /FiO2 below the normality threshold. On the contrary, the HR curve for troponin plasma levels was near-flat with large CI for values above the normality thresholds. Conclusion: In unselected patients hospitalized for COVID-19, mortality is mainly driven by male gender, older age and respiratory failure. Elevated plasma levels of high-sensitivity troponins are not an independent predictor of worse survival when respiratory function is accounted for.